Corporate Social Responsibility as a driver for Consumer’s Loyalty - Ulpah, Maria (Jurnal Manajemen Stratejik dan Simulasi Bisnis, 2023)
The objective of this paper is to find out whether consumer’s perception of Corporate Social Responsibility (CSR) policy of bank will affect the consumer’s loyalty. We tried to see the direct effect of CSR to consumer’s loyalty and the indirect effect to loyalty by using two mediating variables, namely satisfaction and trust, We split the CSR aspect into two main aspects, namely Business CSR and Philanthropic CSR. To test the hypotheses, we carried survey for bank customer who has bank account for more than 3 years. The result found that business CSR had a direct effect and indirect effect to consumer’s loyalty. However, the philanthropic CSR did not have affect the consumer’s trust.